Determinants of exchange rate in Malaysia / Fakhira Abdul Karim - Abdul Karim, Fakhira (Faculty of Business and Management, 2019)
This research attempts to investigate the relationship between the exchange rate and the independent variables, such as, inflation rate, interest rate, foreign direct investment, gross domestic product and money supply in Malaysia. Secondary data was sourced within the period of 1992 Q1 to 2018Q4. On the other hand, the technique that implemented to estimate the model was Multiple Linear Regressions and Granger causality test. The result from Multiple Linear Regressions showed that the determinants factors of exchange rate through interest rate, gross domestic product and money supply is capable of influencing which has an direct relationship and statistically significant to the exchange rate. However, inflation rate and foreign direct investment did not have any relationship with exchange rate. The conclusions for the studies show that interest rate, gross domestic product and money supply become the factors that affecting the exchange rate in Malaysia. From Granger causality test shows that inflation and exchange does not have causality relationship meanwhile for inflation rate and exchange rates have causality to each other knows as bidirectional causality relationship.